2011
DOI: 10.1186/1550-2783-8-13
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of diet consumption, body composition and lipoprotein lipid values of Kuwaiti fencing players with international norms

Abstract: BackgroundNo published data is currently available that describes the dietary patterns or physiological profiles of athletes participating on the Kuwaiti national fencing team and its potential impact on health and physical performance. The purpose of this investigation was to: 1) collect baseline data on nutrient intake 2) collect, analyze and report baseline for body composition, plasma lipid and lipoprotein concentrations during the competitive season, 3) compare the results with the international norms, 4)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 54 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…The current evidence-base on the factors influencing athlete dietary behaviours is somewhat narrowly focused on nutrition knowledge or nutrient intake of specific athlete groups. For example, American football players and fencers (Cole et al, 2005;Ghloum & Hajji, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The current evidence-base on the factors influencing athlete dietary behaviours is somewhat narrowly focused on nutrition knowledge or nutrient intake of specific athlete groups. For example, American football players and fencers (Cole et al, 2005;Ghloum & Hajji, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The similarity in problems such as high protein and fat intakes was found among athletes from many countries. Based on the research data reported in the scientific literature, it has been stated that a diet high in protein and fat, but low in carbohydrates was adopted by professional athletes from countries such as Poland [ 15 , 16 ], Iran [ 17 ], Kuwait [ 18 ], England [ 19 , 20 ], Brazil [ 21 ], Greece [ 22 ], Australia [ 23 , 24 , 25 ], France [ 26 , 27 ] Finland [ 28 ], China [ 29 , 30 ], Ireland [ 31 ], Netherlands [ 32 ], Spain [ 33 , 34 ], the United States of America (USA) [ 35 ], South Africa [ 36 ], Canada [ 37 ]. It has also been found that if athletes consume large amounts of protein and their diets are low in carbohydrates, they can suffer from metabolic acidosis which can adversely affect their physical performance [ 13 , 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…As is the case in other branches of sport, nutrition is also of great importance in fencing. However, there are very few studies on the nutritional attitudes and habits of fencers (11).…”
Section: Introductionmentioning
confidence: 99%